Matrilinearidade e cultura(s) na Índia contemporânea: das culturas tribais à Etnografa e à Etno-Literatura – identidade cultural e representações sociais da “mulher” na sociedade e na cultura indianas - Fitas, Ana Paula (Trabalhos de Antropologia e Etnologia, 2020)
This article aims to contribute, in an interdisciplinary and transdisciplinary perspective, to an anthropological understanding of the identity phenomenon underlying the representation of female social roles and their status in Indian society and culture.